Botanical quality controls and uses of Origanum vulgare L. products and their impact on food security in the province of Jujuy - Argentina - Leila Ayelen Salome GIMENEZ; Nilda Dora Vignale; Marcelo Luis Wagner (International Journal on Food, Agriculture and Natural Resources, 2024)
In Argentina, a nation committed to prioritizing food quality, there is a pressing necessity to fortify quality control systems and establish stringent standards ensuring food safety. This study aims to scrutinize commercial samples of Origanum vulgare L. in the province of Jujuy, Argentine Republic, with the objective of assessing their authenticity and overall quality. Both macroscopic and microscopic techniques were employed to analyze composition and verify identity. Simultaneously, a thorough examination of product labels was conducted to ensure compliance with food regulations. Ethnographic techniques, including merchant interviews, were utilized to gather comprehensive insights. The findings reveal considerable variability in the composition of "oregano" samples, with instances of foreign elements such as stones and dust detected in some cases. Microscopic identification unequivocally confirmed the presence of contaminating elements. Notably, the majority of industrial products adhered to labeling standards, while a mere 10% of artisanal samples achieved similar compliance. The study also unveiled diverse culinary and medicinal applications for the examined oregano samples. These discoveries underscore the imperative for heightened oversight to guarantee the quality and purity of oregano products. The correlation between microscopic results and previous studies bolsters the reliability of this analytical approach. In conclusion, the study emphasizes the paramount importance of instituting policies and programs that advance food security. The proposed methodology emerges as an effective means to enhance quality control in the marketing of plant products in the province.